Asset Allocation and Quality in the Banking System: The Case of Uzbekistan - Ro’ziev Bakhtiyor Salimboevich (Scientific Trends, 2025)
This paper analyzes the asset allocation and quality of commercial banks in Uzbekistan during 2020–2025. Using macroeconomic indicators, loan-to-GDP ratios, capital adequacy, deposit dynamics, non-performing loan (NPL) trends, and profitability measures, the study evaluates the efficiency of financial intermediation and its impact on economic development. The findings indicate that although banking assets nearly doubled over the period, their share in GDP declined, reflecting weaker financial intermediation. NPL ratios fluctuated significantly, peaking at 5.2% in 2022, which directly undermined profitability indicators such as return on assets (ROA) and return on equity (ROE). The monetization coefficient remained relatively low at 22.8% in 2025 compared to international standards, indicating underdeveloped financial deepening. The study concludes that structural reforms are required to enhance risk management, diversify funding sources, and improve the alignment between banking assets and the real economy. Recommendations include strengthening credit monitoring, expanding long-term deposits, improving asset allocation to productive sectors, and gradually lowering refinancing rates in line with inflationary conditions.
Keywords: Uzbekistan banking system; asset quality; financial intermediation; non-performing loans; profitability indicators; monetization ratio; refinancing rate; credit portfolio management.